Optimal portfolio size for portfolio diversification : an empirical study on Singapore Stock Exchange. - Chong, Wai Lam. (2011)
Our study investigates the optimal number of securities one should hold in a portfolio, consisting of the securities listed on the Singapore Stock Exchange (SGX), for different investment horizons under a set of assumptions.